The Effect of Corporate Social Responsibility Disclosure, Leverage, and Company Size on Company Value with Profitability as a Moderating Variable (Case Study of Energy Sector Companies Listed on the IDX in 2020-2023) - Riska Huliawati; Netty Herawaty; Wiwik Tiswiyanti (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of Corporate Social Responsibility (CSR), leverage, and company size on firm value, with profitability as a moderating variable. The study population comprised energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study employed a quantitative method with secondary data in the form of company annual reports. The results show that CSR has a positive effect on firm value. Leverage has a negative effect on firm value. Company size has a positive effect on firm value. Profitability moderates the influence of CSR, leverage, and company size on firm value